Search for Compounds with Hypoglycemic Activity in the Series of 1-[2-(1H-Tetrazol-5-yl)-R(1)-phenyl]-3-R(2)-phenyl(ethyl)ureas and R(1)-Tetrazolo[1,5-c]quinazolin-5(6H)-ones - Antypenko, Oleksii M. (Sci Pharm, 2016)
Methods of 1-[2-(1H-tetrazol-5-yl)-R(1)-phenyl]-3-R(2)-phenyl(ethyl)ureas and R(1)-tetrazolo[1,5-c]quinazolin-5(6H)-ones synthesis were designed. IR, LC-MS, (1)H NMR, and elemental analysis data evaluated the structure and purity of the obtained compounds. Different products, depending on the reaction conditions, were distinguished and discussed. The preliminary hypoglycemic activity of 36 synthesized compounds was revealed. Docking studies to 11β-hydroxysteroid dehydrogenase 1, γ-peroxisome proliferator-activated receptor, and dipeptidyl peptidase-4 were conducted. Eight of these substances were further tested on glucocorticoid-induced insulin resistance models, namely glucose tolerance, oral rapid insulin, and adrenalin tests. One of the most active compounds turned out to be tetrazolo[1,5-c]quinazolin-5(6H)-one 3.1, exceeding the reference drugs Metformin (50 and 200 mg/kg) and Gliclazide (50 mg/kg).